Nickel/Biochar from Palm Leaves Waste as Selective Catalyst for Producing Green Diesel by Hydrodeoxygenation of Vegetable Oil - Galih Dwiki Ramanda; Allwar Allwar; Muchammad Tamyiz; Is Fatimah; Ruey-an Doong (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
The objective of this research was to prepare low-cost catalyst for green diesel conversion from vegetable oil. The catalyst of nickel-dispersed biochar (Ni/BC) was prepared by direct pyrolysis of nickel precursor with palm leaves waste under N2 stream at 500 °C. The obtained catalyst was examined by using x-ray diffraction, scanning electron microscope-energy dispersive x-ray, transmission electron microscopy, gas sorption analysis, FTIR and surface acidity examination. The catalytic activity testing was performed on rice bran oil hydrodeoxygenation at varied temperature and time of reaction. Based on analyses, the results showed the successful preparation of Ni/BC with the characteristic of single nickel nanoparticles decorated on surface. The increasing specific surface area of material was conclusively remarked the surface area enhancement by nickel dispersion along with the increased surface acidity, suggesting that the material can be applied for acid catalysis applications. The Ni/BC exhibited excellent catalytic conversion of rice bran oil with the high selectivity toward diesel fraction with 85.3% yield and 92.6% selectivity. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).